Vasopressin Differentially Affects Handgrip Force of Expectant Fathers in Reaction to Own and Unknown Infant Faces - Alyousefi-van Dijk, Kim; van ‘t Veer, Anna E.; Meijer, Willemijn M.; Lotz, Anna M.; Rijlaarsdam, Jolien; Witteman, Jurriaan; Bakermans-Kranenburg, Marian J. (Frontiers in Behavioral Neuroscience, 2019)
The underlying mechanisms of paternal responses to infant signals are poorly understood. Vasopressin has previously been proposed to affect these responses. Using a double-blind, placebo-controlled, within-subject design (N = 25 expectant fathers), we examined the effect of vasopressin administration on the use of excessive handgrip force during exposure to infant crying versus matched control sounds, while participants saw morphed images representing their own infant versus an unknown infant. We found that, compared to placebo, AVP administration elicited more excessive force while viewing an unknown infant image compared to viewing the image representing one’s own infant, while the reverse was true under placebo. The results are discussed in light of vasopressin’s role in parenting and parental protection among human fathers.